The role of family firm specific resources in innovation: an integrative literature review and framework - Anne Heider; Marcel Hülsbeck; Leopold von Schlenk-Barnsdorf (Management Review Quarterly, 2022)
Family firms are the prevalent form of entrepreneurial organizations worldwide. While even long-lasting and successful family firms are said to invest less in innovation, their innovation output varies according to their heterogeneity often matching or even exceeding the output of other incumbent firms. These contradictory results have confused entrepreneurship and innovation researchers alike. Based on an integrative literature review we develop a conceptual framework to explain the role of family firm specific resources for innovation. Our analysis of 48 peer-reviewed empirical articles drawn from a body of 466 published empirical papers shows how our integrative perspective helps to solve these existing contradictions. We argue that higher investments into these family firm specific resources trigger a virtuous circle in family firm innovation.
Keywords: L10; L26; O30; 650; Entrepreneurial firms; Family firm; Innovation; Family firm resources; Conceptual framework